Effectiveness of audit committees in the Turkish banking sector - Sarıçam ,Yıldıray (My University, 2009)
Kurumsal Yönetim, Denetim Komitesi. ZET Bu çalışmada denetim komitesi etkinliğini oluşturan özelliklerle (denetim komitesindeki üye sayısı, denetim komitesindeki üyelerin bağımsızlığı, denetim komitesi toplantı sayısı, denetim komitesi üyelerinin finansal deneyimi, denetim komitesi üyelerinin eğitim seviyesi, yaşları ve tecrübe yılları) banka performansını ölçen (aktif karlılığı, özsermaye karlılığı ve ner faiz marjı) oranları ilişkilendirerek Türk bankacılık sektöründe denetim komitelerinin etkinliğini ölçmeye amaçladım. Çalışmanın veri seti Türkiye Bankalar Birliği’nin internet sitesinde yer alan 28 banka ve yine 5411 sayılı Bankacılık Kanunu’na tabi olan 4 katılım bankasının 2007 yılına ait faaliyet raporlarından elde edilmiştir. Sonuçta denetim komitesi üye sayısı ve üyelerin eğitim seviyeleri ile aktif karlılığı; denetim komitesinin bağımsızlığı ve üyelerin eğitim seviyesi özsermaye karlılığı; üyelerin yaşları da net faiz marjıyla ilişkili çıkmıştır. : Corporate Governance, Audit Committee. Key Words

In this dissertation I aim to associate characteristics of audit committee effectiveness (number of members in audit committee, independence proportion of members in audit committee, number of audit committee meetings, financial expertise of members in audit committee, education level of members in audit committee, age and experience of members in audit committee) with bank performance in the means of bank measure ratios (ROA, ROE and NIM) in the Turkish banking sector. The sample consists of 28 banks that classified on the official site of the Banks Association of Turkey and 4 Private Finance Houses which are also subjected to the Banking Law No. 5411. I gathered data from banks’ annual reports and used regression analysis to investigate the relationship. I have found relations between some characteristics of audit committee effectiveness and bank performance indicators, even though they are not strongly associated or their contribution may be limited; number of directors, education level, independence proportion and age of members in the audit committee are related with the ROA, ROE and NIM respectively.
Keywords: Bankalar ve Bankacılık; Kurumsal Yönetim; Muhasebe